MRI and Active Surveillance for Prostate Cancer - Angelo Porreca; Michele Colicchia; Gian Maria Busetto; Matteo Ferro (Diagnostics, 2020)
Since the introduction of Prostate-Specific Antigen (PSA) screening, prostate cancer mortality has decreased [...]